Understanding the dynamics of broadband markets: A comparative case study of Flanders and the Netherlands - Marlies Van der Wee; Sofie Verbrugge; Wolter Lemstra (International Telecommunications Society (ITS), 2012)
The Digital Agenda for Europe sets out clear goals for providing high speed broadband to all its residents, but leaves the implementation of this plan to the individual Member States. Because of large economic, cultural and political differences, the roads to realizing these ambitious goals are varying in between these Member States. This paper investigates the dynamics of fixed broadband markets in two neighboring regions: Flanders, the northern part of Belgium, and the Netherlands. The historical developments in telecom markets in both regions are highly similar and resulted in both areas in a duopoly between the incumbent, operating DSL on the former telephone network, and one or more cable operators, using the DOCSIS technology to offer broadband on the former analogue television network. However, in the race towards realizing the Digital Agenda goals, it comes down to the small differences in between both regions: the existence of housing organizations in the Netherlands has led to quite some Fiber-to-the-Home deployment, whereas in Flanders, the traditional operators use evolutionary upgrades of both DSL and DOCSIS to realize the European targets.
Keywords: 330; Telecom infrastructure; market dynamics; regulation; broadband; DSL; cable; FttH